PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN SATUAN PENGAMANAN PT TUNAS ARTHA GARDATAMA AREA TUGAS BANK BCA DKI JAKARTA - Abdul Rahman Safiih; Haerul Okta Fahmi (Gapenas Publisher, 2023)
This study aims to determine the effect of compensation and organizational culture on guard performance at PT Tunas Artha Gardatama BCA DKI Jakarta Assignment Area. This study uses quantitative methods that are associative (causal). The research population was all employees at PT Tunas Artha Gardatama BCA DKI Jakarta Assignment Area, amounting to 140 people, while in determining the research sample using slovin sampling technique with error rate 5% of the total population, a sample of 104 respondents was obtained. Data analysis and testing techniques include multiple correlation analysis, coefficient of determination, multiple linear regression, validity and reliability tests, classical assumption tests, and hypothesis testing. Referring to the test results, it can be seen that the multiple correlation coefficient is 0,958 and is considered to be very strong. While the coefficient of determination or contribution of compensation and organizational culture to guard performance is is 90,7% on guard performance. And the rest 9,3% was effected by other variable outside of this research. Based on the results of the first hypothesis test, namely the effect of compensation on guard performance, the value tcount > ttable or 9,298 > 1,990, meaning that partially there is a significant influence between compensation on guard performance at PT Tunas Artha Gardatama BCA DKI Jakarta Assignment Area. While the second hypothesis test is the influence of organizational culture on guard performance, the value of tcount > ttable or 7,784 > 1,990, meaning that partially there is a significant influence between organizational culture on guard performance at PT Tunas Artha Gardatama BCA DKI Jakarta Assignment Area. The results of the third hypothesis test obtained the value of Fcount > Ftable or 502.184 > 3.090, meaning that simultaneously compensation and organizational culture have a significant effect on guard performance at PT Tunas Artha Gardatama BCA DKI Jakarta Assignment Area. While the multiple linear regression analysis obtained the equation that is Y = 0,991 + 0,539X1 + 0,320X2